Interdependent Patient-Reported Outcome Patterns During Breast Cancer Pharmacotherapy: A Correlation-Based Analysis Using EORTC QLQ-C30 and QLQ-BR23 - Sutanto, Henry; Savitri, Merlyna; Ashariati, Ami; Hendarsih, Een (Asian Pacific Journal of Cancer Biology, 2026)
Background: Quality-of-life (QoL) assessment is essential in breast cancer care, yet limited evidence describes how interrelated QoL domains change during pharmacotherapy. This study aimed to evaluate correlations among functional and symptom scales using the EORTC QLQ-C30 and QLQ-BR23, highlighting their ability to reveal multidimensional QoL patterns. Methods: A prospective observational study was conducted in two second-referral hospitals in Indonesia, enrolling 106 female breast cancer patients. QoL was assessed before and after pharmacotherapy using QLQ-C30 and QLQ-BR23. Changes in scores (Δ) were computed, and interdomain relationships were analyzed using Spearman’s rho. Results: Physical functioning correlated with role functioning (ρ = 0.55, p <0.001), emotial functioning (ρ = 0.33, p <0.001), and social functioning (ρ = 0.31, p = 0.002). Role and social functioning were likewise correlated (ρ = 0.32, p = 0.001), indicating that improvements across functional domains tended to occur in parallel. Symptom scales showed strong positive clustering, including fatigue with pain (ρ = 0.37, p <0.001), insomnia (ρ = 0.35, p <0.001), and systemic side effects (ρ = 0.48, p <0.001). Functional and symptom domains generally exhibited inverse relationships: physical functioning negatively correlated with fatigue (ρ = –0.40), pain (ρ = –0.43), both p <0.001, and systemic side effects (ρ = –0.26; p = 0.01). Conclusion: The QLQ-C30 and QLQ-BR23 instruments effectively captured structured, clinically meaningful interdependencies. Functional improvements consistently aligned with symptom reductions, revealing coherent functional–symptom clustering. These findings underscore the sensitivity of QoL vinstruments to detect multidimensional patient-reported changes during breast cancer pharmacotherapy.